2014
DOI: 10.3389/fphar.2014.00177
|View full text |Cite
|
Sign up to set email alerts
|

Drug elucidation: invertebrate genetics sheds new light on the molecular targets of CNS drugs

Abstract: Many important drugs approved to treat common human diseases were discovered by serendipity, without a firm understanding of their modes of action. As a result, the side effects and interactions of these medications are often unpredictable, and there is limited guidance for improving the design of next-generation drugs. Here, we review the innovative use of simple model organisms, especially Caenorhabditis elegans, to gain fresh insights into the complex biological effects of approved CNS medications. Whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…The neurotransmitter and drug concentrations evaluated in these experiments were based on either standard values from the literature or levels found effective for other drugs of the same general class [24,25]. The drug and control plates were allowed to dry and equilibrate for 2-3 h prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The neurotransmitter and drug concentrations evaluated in these experiments were based on either standard values from the literature or levels found effective for other drugs of the same general class [24,25]. The drug and control plates were allowed to dry and equilibrate for 2-3 h prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Simple model organisms, including C. elegans , have proven valuable for investigating mechanisms of action of psychotropic drugs and identification of new targets of these drugs [recently reviewed in [55]]. In fact, it has been both surprising and encouraging that so many drugs originally optimized to treat human psychiatric illness also show potent activity in C. elegans against disease-relevant behaviors.…”
Section: Psychiatric Drugs In C Elegansmentioning
confidence: 99%
“…C. elegans has already been instrumental for the identification of new targets and signaling pathways affected by CNS drugs [55]. For example, studies of clozapine revealed that it binds to the trace amine-associated receptor TAAR1, which was then implicated in clozapine enhancement of PPI [56].…”
Section: Psychiatric Drugs In C Elegansmentioning
confidence: 99%
“…Apart from blocking the receptors traditionally explaining the antipsychotic action of atypical APDs, CLO possesses an affinity for the full range of receptors: serotonin, dopamine, adrenergic, cholinergic and histaminic [4] , as well as ion channels, transporters and other molecules [4,5] . CLO also differentially changes the expression of numerous genes [6,7] .…”
Section: Introductionmentioning
confidence: 99%